2011
DOI: 10.5021/ad.2011.23.s2.s258
|View full text |Cite
|
Sign up to set email alerts
|

Steatocystoma Multiplex Confined to the Scalp with Concurrent Alopecia

Abstract: Steatocystoma multiplex (SM) is an uncommon disorder of the pilosebaceous unit characterized by the development of numerous sebum-containing dermal cysts which rarely involves the scalp. Here, we report a case of a 50-year-old man with multiple cystic nodules and alopecic patches on his scalp. On histopathological examination, the folded cyst was found to be lined by stratified squamous epithelium, while flattened sebaceous gland cells were identified in the cystic wall. Pigment casts were present in the hair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Characteristically, it presents with multiple skin-colored dermal cysts on the trunk, axilla, groin, and proximal extremities [1]. In the literature, however, there are rare SM presentations reported for the breasts, face [15, 16], and scalp [17, 18], but in most of these atypical cases, the lesions were localized and limited to a single anatomical location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristically, it presents with multiple skin-colored dermal cysts on the trunk, axilla, groin, and proximal extremities [1]. In the literature, however, there are rare SM presentations reported for the breasts, face [15, 16], and scalp [17, 18], but in most of these atypical cases, the lesions were localized and limited to a single anatomical location.…”
Section: Discussionmentioning
confidence: 99%
“…They classified the typical form as mostly hereditary, appearing in childhood and early adulthood, with SM limited to the scalp as being sporadic and appearing in late adulthood. Lee et al [17] reported sporadic cases of SM presentation limited to the scalp, with alopecia patches due to trichotillomania.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] SM of the scalp with concurrently acquired alopecia secondary to trichotillomania has been reported. [ 21 ] The occurrence of multiple SM is reported in a psoriasis patient on ustekinumab treatment. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Steatocystoma multiplex is characterized by the development of numerous steatocystomas involving areas that are anatomically rich in sebaceous glands, such as the chest, arms, axillae and neck. However, cases involving the scalp, the retroauricular region, the groin, the nose or even the acral areas have also been described.…”
mentioning
confidence: 99%